Inhibitory Capacity of Clay Mask 96% Ethanol Extract from Bitter Melon (Momordica charantia L.) Against Staphylococcus aureus - I Gusti Ayu Manik Widhyastini; Devy Susanty; Siti Qur'aniati (Universitas Nusa Bangsa, 2022)
Momordica charantia L. commonly known as bitter melon plant, is widely used as a treatment for various diseases, including skin infections. The purpose of this study was to determine the highest concentration of bitter melon extract and infusion in inhibiting the growth of Staphylococcus aureus bacteria. This research was conducted using the disc diffusion method and evaluation of the quality of the clay mask was carried out on the growth of Staphylococcus aureus bacteria. The results showed that 96 % ethanol extract of bitter melon at a concentration of 100% had an inhibitory effectiveness of 6.32 mm and was higher than that of 4.85 mm of bitter melon infusion. The clay mask formula of 96% ethanol extract of bitter melon with concentrations of 5 % (F1), 7.5 % (F2) and 10 % (F3) gave a fairly good evaluation of physical quality with an inhibition zone of 5.0 mm; 7.06 mm and 7.30 mm, respectively. The clay mask of 96% ethanol extract of bitter melon fruit F1, F2 and F3 belongs to the medium category in inhibiting bacteria.keywords: inhibition; ethanol extract; clay mask; Momordica charantia L.; Staphylococcus aureusABSTRAKDaya Hambat Masker Clay Ekstrak Etanol 96% Buah Pare (Momordica charantia L.) terhadap Bakteri Staphylococcus aureusMomordica charantia L. umumnya dikenal dengan tanaman pare, digunakan sebagai pengobatan terhadap berbagai penyakit, diantaranya infeksi pada kulit. Penelitian ini bertujuan untuk mengetahui konsentrasi tertinggi ekstrak dan infusa buah pare dalam menghambat pertumbuhan bakteri Staphylococcus aureus. Penelitian ini dilakukan menggunakan metode difusi cakram dan evaluasi mutu masker clay dilakukan terhadap pertumbuhan bakteri Staphylococcus aureus. Hasil penelitian menunjukkan bahwa ekstrak etanol 96 % buah pare pada konsentrasi 100 % memiliki efektivitas daya hambat sebesar 6,32 mm dan lebih tinggi dibandingkan dengan infusa buah pare 4,85 mm. Formula masker clay ekstrak etanol 96 % buah pare konsentrasi 5 % (F1) ; 7,5 % ; (F2) dan 10 % (F3) memberikan hasil evaluasi mutu fisik yang cukup baik dengan zona hambat berturut-turut 5,0 mm ; 7,06 mm dan 7,30 mm. Masker clay ekstrak etanol 96% buah pare F1, F2 dan F3 termasuk ke dalam kategori sedang dalam menghambat bakteri.Kata kunci: daya hambat; ekstrak etanol; masker clay; Momordica charantia L.; Staphylococcus aureus